2022
DOI: 10.1111/imj.15146
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with delayed surveillance colonoscopy

Abstract: Background: Surveillance colonoscopy has been shown to be an effective tool for prevention of colorectal cancer (CRC) in high-risk populations, if adhered to.Aim: To discover the sequelae of late surveillance in a cohort of patient's overdue for colonoscopy. Methods:We conducted a retrospective cohort study on all patients from the Bay of Plenty District Health Board region, New Zealand, placed on the colonoscopy surveillance waitlist from 2006 onwards who had their procedure completed between 1 November 2016 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 29 publications
(62 reference statements)
0
5
1
Order By: Relevance
“…The results of our study will help clarify for clinicians and patients the risk of colonoscopy delay. A recent study has shown that a 1-year delay in surveillance colonoscopy in patients with a prior history of polyps was associated with a 19% increase in the risk of advanced adenomas, 32 which is even greater than that in our study likely reflecting the at-risk patient population of the study. Prior literature has also described increased disease progression and mortality associated with delays in diagnostic colonoscopy after positive fecal screening tests 33–35 .…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The results of our study will help clarify for clinicians and patients the risk of colonoscopy delay. A recent study has shown that a 1-year delay in surveillance colonoscopy in patients with a prior history of polyps was associated with a 19% increase in the risk of advanced adenomas, 32 which is even greater than that in our study likely reflecting the at-risk patient population of the study. Prior literature has also described increased disease progression and mortality associated with delays in diagnostic colonoscopy after positive fecal screening tests 33–35 .…”
Section: Discussioncontrasting
confidence: 71%
“…The risk in high-risk patients such as those with a family history of CRC remains unclear although it would be expected to be even greater. 32 Furthermore, it is possible that some of the participants may have had symptoms or clinical indications that may have led to the colonoscopy that could not be found by chart review. We were also unable to identify the causes of the delay in performing the initial screening colonoscopy, so studies assessing barriers or causes of the delay are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Strict adherence to these surveillance recommendations is at times variable due to patient reticence or service delivery factors 5 . Currently, pressures on medical services during the COVID‐19 pandemic and resultant delays to surveillance colonoscopies also have the potential to increase the risk of developing advanced preinvasive lesions, or CRC and related death 6–9 …”
Section: Introductionmentioning
confidence: 99%
“…5 Currently, pressures on medical services during the COVID-19 pandemic and resultant delays to surveillance colonoscopies also have the potential to increase the risk of developing advanced preinvasive lesions, or CRC and related death. [6][7][8][9] The consequences of delays in surveillance colonoscopy procedures of elevated-risk patients have not been widely investigated. Observations in other patient cohorts have demonstrated that a 2to 6-month delay in colonoscopy in symptomatic patients can increase the odds of advanced neoplasia 7 and can lead to significantly higher mortality rates and loss of life years, 10 while in faecal immunochemical test (FIT)-based screening populations, an increased risk of advanced CRC is related to a delay in colonoscopy beyond 4-6 months, and mortality from CRC increases with more than a 12-month delay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation